INFLUENCE OF GROSS REGIONAL DOMESTIC PRODUCT (GDP) AND INVESTMENT AGAINST POVERTY IN EAST KALIMANTAN PROVINCE - Ningrum, Rr. Tri Gunarti; Jainuddin, Jainuddin (Journal Competency of Business, 2023)
This research aims to determine the influence of Gross Regional Domestic Product (GRDP) and investment on poverty in East Kalimantan Province. The data used is time series data for 16 years (2007-2022) and analyzed using a multiple regression model. The research results show that GRDP has a significant negative effect on poverty, while investment has a positive direction and has no effect on poverty. Furthermore, the GRDP and investment variables simultaneously significantly affect poverty. It is hoped that the government will further optimize GRDP sectors and equalize investment to reduce poverty in East Kalimantan Province.